Radiosensitizing effect of intratumoral interleukin-12 gene electrotransfer in murine sarcoma - Sedlar Ales; Kranjc Simona; Dolinsek Tanja; Cemazar Maja; Coer Andrej; Sersa Gregor (BMC Cancer, 2013)
Abstract Background Interleukin-12 (IL-12) based radiosensitization is an effective way of tumor treatment. Local cytokine production, without systemic shedding, might provide clinical benefit in radiation treatment of sarcomas. Therefore, the aim was to stimulate intratumoral IL-12 production by gene electrotransfer of plasmid coding for mouse IL-12 (mIL-12) into the tumors, in order to explore its radiosensitizing effect after single or multiple intratumoral gene electrotransfer. Methods Solid SA-1 fibrosarcoma tumors, on the back of A/J mice, were treated intratumorally by mIL-12 gene electrotransfer and 24 h later irradiated with a single dose. Treatment effectiveness was measured by tumor growth delay and local tumor control assay (TCD50 assay). With respect to therapeutic index, skin reaction in the radiation field was scored. The tumor and serum concentrations of cytokines mIL-12 and mouse interferon γ (mIFNγ) were measured. Besides single, also multiple intratumoral mIL-12 gene electrotransfer before and after tumor irradiation was evaluated. Results Single intratumoral mIL-12 gene electrotransfer resulted in increased intratumoral but not serum mIL-12 and mIFNγ concentrations, and had good antitumor (7.1% tumor cures) and radiosensitizing effect (21.4% tumor cures). Combined treatment resulted in the radiation dose-modifying factor of 2.16. Multiple mIL-12 gene electrotransfer had an even more pronounced antitumor (50% tumor cures) and radiosensitizing (86.7% tumor cures) effect. Conclusions Single or multiple intratumoral mIL-12 gene electrotransfer resulted in increased intratumoral mIL-12 and mIFNγ cytokine level, and may provide an efficient treatment modality for soft tissue sarcoma as single or adjuvant therapy to tumor irradiation.